Yesterday's expectation of tomorrow determines what you do today: the role of reference-dependent utility from expectations - Astrid Matthey (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
The paper introduces the concept of adjustment utility, that is, referencedependent utility from expectations. It offers an explanation for observed preferences that cannot be explained with existing models, and yields new predictions for individual decision making. The model gives a simple explanation for, e.g., why people are reluctant to change their plans even when these turn out to be unexpectedly costly; peoples aversion towards positive but false information, which cannot be explained with previous models; and the increasing acceptance of risks when people get used to them.
Keywords: D11; D81; D84; C99; 330; utility; expectations; reference-dependent preferences; anticipation; prospect theory; experiments; Entscheidung bei Unsicherheit; Erwartungstheorie; Präferenztheorie; Theorie